2008
DOI: 10.1248/cpb.56.692
|View full text |Cite
|
Sign up to set email alerts
|

Light Irradiation Is a Factor in the Bactericidal Activity of Silver-Loaded Zeolite

Abstract: Silver loaded zeolite (Ag-Z) was previously found to have effective bactericidal activity against Escherichia coli. To understand the mechanisms of bactericidal activity of Ag-Z, role of light irradiation was focused and investigated in this study. In this study, we focused on light irradiation. Antibacterial assay and spectroscopic study revealed that light irradiation enabled Ag-Z to reduce dioxygen to form a reactive oxygen species, which led to bactericidal activity. These results indicate that the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This is affected by the presence of Ag + -ions which are incorporated and dispersed into the material. It was not only the concentration of the activating agent, since zeolite had the lowest sorption capacity for Ag + -ions, comparing with GAC and T sorbents, as presented in Table 1, but also the accessibility and distribution of Ag + -ions resulted in the efficient antimicrobial activity [5].…”
Section: Antimicrobial Activity Of Ag + -Activated Sorbentsmentioning
confidence: 99%
“…This is affected by the presence of Ag + -ions which are incorporated and dispersed into the material. It was not only the concentration of the activating agent, since zeolite had the lowest sorption capacity for Ag + -ions, comparing with GAC and T sorbents, as presented in Table 1, but also the accessibility and distribution of Ag + -ions resulted in the efficient antimicrobial activity [5].…”
Section: Antimicrobial Activity Of Ag + -Activated Sorbentsmentioning
confidence: 99%
“…As compared with the organic ones, inorganic antibacterial materials have advantages in terms of the durability, safety, chemical stability and thermal resistance [1][2][3][4]. These materials are generally based in metallic ions, such as Ag + , Cu 2+ and Zn 2+ , among which silver is well known to have a great and broad spectrum antibacterial activity and relatively high safety [5][6][7][8][9]. Recently, various antibacterial materials containing silver, such as Agmontmorillonite, Ag-zeolite, Ag-SiO 2 and Ag-polymer fibers have been prepared [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Light is necessary to elicit the antibacterial activity of Ag-Z [9]. We focused on the oxidation state of silver in this study because light irradiation may lead to the reduction of silver ions in systems containing Ag-Z.…”
Section: Resultsmentioning
confidence: 99%
“…Ag-Z in water causes dissolved dioxygen to form reactive oxygen species. We also reported that light irradiation was necessary to form reactive oxygen species [9].…”
Section: Introductionmentioning
confidence: 90%